A quantitative remote sensing investigation of ecosystem health in aquatic habitats, concentrating on China's Heihe River Basin - XU HONGMEI, XU HONGMEI; DR MOHAMMED SALEH NUSARI, DR MOHAMMED SALEH NUSARI; DR HJ ARAZI BIN IDRUS, DR HJ ARAZI BIN IDRUS (International Journal of Multidisciplinary Research and Studies, 2024)
To explain (1) how hydrological processes affect the distribution and structure of biological systems, and (2) how biological systems influence the water cycle," as stated by ecohydrologists, is the primary "goal of ecohydrology" (Baird and Wilby, 1999; Rodriguez-Iturbe, 2000; Bonell, 2002; Eagleson, 2002; Kundzewicz, 2002; Nuttle, 2002; Zalewski, 2002; Bond, 2003; Hunt and Wilcox, 2003; Newman et al., 2003; Van Dijk, 2004; Hannach" et al., 2004; Breshears, 2005). Consequently, the study of the ecological impacts of hydrology is known as ecohydrology. " One of the first steps in developing an ecohydrological approach to water resources management is gaining a deeper understanding of and a means of quantifying the relationship between plants and water. Managing watersheds in arid regions continues to attract attention in the face of dwindling water supplies (Hibbert, 1983). If accurate correlations can be established between groundwater recharge, runoff, hydraulic variables, and the change in vegetation, then these operations can be used as proxies for water demand (Walvoord and Phillips, 2004; "Kwicklis et al., 2005). Vegetation is known to have a significant role in the dynamics of groundwater recharge and outflow in arid regions, and this has been studied using remote sensing techniques (Cayrol et al., 2000; Kerkhoff et al., 2004b). To foretell surface flow and groundwater recharge, vegetation mapping can be utilized instead of surface and subsurface sampling and analysis. Predicting the vegetation's response to changes in water input and the vegetation's impact on water fluxes requires ecohydrological approaches and models that make use of remote sensing technology "and stowing away Improving satellite remote sensing capabilities may help us learn more about the vegetation's response to shifts in hydrological processes. Understanding ecohydrological processes requires integrating remote sensing methods with hydrology.